2016
DOI: 10.18632/oncotarget.10184
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for 1,4-Benzoquinone-induced genotoxicity

Abstract: Benzene is a common environmental toxin and its metabolite, 1-4-Benzoquinone (BQ) causes hematopoietic cancers like myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). BQ has not been comprehensively assessed for its impact on genome maintenance, limiting our understanding of the true health risks associated with benzene exposure and our ability to identify people with increased sensitivity to this genotoxin. Here we analyze the impact BQ exposure has on wild type and DNA repair-defective mouse em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…To further investigate the structural features that TOP2 recognizes, and to identify factors which influence such features, will change how we evaluate the effect of many anti-TOP2 chemotherapeutic agents. In addition, environmental agents like benzene ( 88 ) and phytochemicals in food and natural products ( 89 ) are known to generate TOP2-induced breaks, and identifying regions prone to these stresses will have a broad impact on our understanding of human genome instability.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the structural features that TOP2 recognizes, and to identify factors which influence such features, will change how we evaluate the effect of many anti-TOP2 chemotherapeutic agents. In addition, environmental agents like benzene ( 88 ) and phytochemicals in food and natural products ( 89 ) are known to generate TOP2-induced breaks, and identifying regions prone to these stresses will have a broad impact on our understanding of human genome instability.…”
Section: Discussionmentioning
confidence: 99%
“…1,4-BQ increased the DNA damage in both K562-PTP4A3 − cells and K562-NC cells in a dose-dependent manner. 1,4-BQ could cause DNA damage through suppressing type 1 topoisomerases [41]. DNA damage was higher in K562-PTP4A3 − cells than K562-NC cells at a low dose 1,4-BQ (10 µM).…”
Section: Discussionmentioning
confidence: 94%
“…For the molecular and cellular mechanisms underlying BQ hematotoxicity, several molecular pathways have been proposed, such as type 1 topoisomerases (Son et al, 2016). It has been shown that BQ modulates the fate of HSPCs by altering the self-renewal- and differentiation-related genes, such as Bmi-1 and GATA3 (Chow et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies have shown that exposure of murine hematopoietic stem and progenitor cells (HSPCs) to BQ interferes with their physiological properties and changes their clonogenic potency by altering genes for apoptosis, DNA repair, cell cycle, self-renewal and differentiation (Chow et al, 2018; Faiola et al, 2004). Son et al (2016) analyzed the impact that BQ exposure has on DNA-repair-defective mouse embryonic stem cells. They proposed that BQ suppresses type 1 topoisomerases to inhibit replication fork restart and progression, leading to chromosomal instability that has the potential to cause hematopoietic disorders.…”
Section: Introductionmentioning
confidence: 99%